Informal Firms and Financial Inclusion : Status and Determinants - Farazi, Subika (World Bank, Washington, DC, 2014)
Many firms in the developing world -- including a majority of micro, small, and medium enterprises -- operate in the informal economy. The informal firms face a variety of constraints, making it harder for them to do business and grow. Lack of access to finance is often cited as the biggest operational constraint these firms face. This paper documents the use of finance and financing patterns of informal firms, highlights differences between use of finance by formal and informal firms, and identifies the most significant characteristics of informal firms that are associated with higher use of financial services. The analysis shows that use of loans and bank accounts for business by informal firms is very low and a vast majority finances their day-to-day operations and investments through sources other than financial institutions (internal funds, moneylenders, family, and friends). A majority of informal firm owners would like their firms to become formal but do not do so as it would require them to pay taxes. Registered firms are 54 percent more likely to have a bank account and 32 percent more likely to have loans. Results also show that firm size, the level of education of the owner, and whether the owner has a job in the formal sector are significantly associated with financial inclusion of informal firms.